Low-power concentrating solar cell - XIONG YONGJUN (2016)
The invention discloses a low-power concentrating solar cell. A common solar unit photocell is arranged on the concentrating surface of a light funnel; and a copper layer, an insulation layer and a heat dissipation plate are arranged on the bottom surface of the cell. When vertically irradiating on a lighting surface of the light funnel, the sunlight irradiates on a concentrating surface through a reflection film on the side face of the light funnel and then the reflected sunlight is overlapped with direct sunlight, so that the photocell on the concentrating surface can obtain irradiation of several times of sunlight, the output capability of the photocell is multiplied, the using amount of the photocell is greatly decreased, and the photovoltaic power generation cost is greatly reduced. 种低倍聚光太阳能电池，它是在光漏斗的聚光面上安装普通的太阳能单元光电池，电池的底面设置敷铜层、绝缘层和散热板。当阳光垂直射入光漏斗的采光面上时，经光漏斗侧面的反光膜使阳光射入其聚光面，再与直射太阳光叠加，使装在聚光面上的光电池得到几倍于太阳光的照射，光电池输出能力成倍增加，光电池的用量大为减少，光伏发电的成本大幅降低。